Characterization of SALL2 Gene Isoforms and Targets Across Cell Types Reveals Highly Conserved Networks - Farkas, Carlos; Quiroz, Aracelly; Alvarez, Claudia; Hermosilla, Viviana; Aylwin, Carlos F.; Lomniczi, Alejandro; Castro, Ariel F.; Hepp, Matias I.; Pincheira, Roxana (Frontiers in Genetics, 2021)
The SALL2 transcription factor, an evolutionarily conserved gene through vertebrates, is involved in normal development and neuronal differentiation. In disease, SALL2 is associated with eye, kidney, and brain disorders, but mainly is related to cancer. Some studies support a tumor suppressor role and others an oncogenic role for SALL2, which seems to depend on the cancer type. An additional consideration is tissue-dependent expression of different SALL2 isoforms. Human and mouse SALL2 gene loci contain two promoters, each controlling the expression of a different protein isoform (E1 and E1A). Also, several improvements on the human genome assembly and gene annotation through next-generation sequencing technologies reveal correction and annotation of additional isoforms, obscuring dissection of SALL2 isoform-specific transcriptional targets and functions. We here integrated current data of normal/tumor gene expression databases along with ChIP-seq binding profiles to analyze SALL2 isoforms expression distribution and infer isoform-specific SALL2 targets. We found that the canonical SALL2 E1 isoform is one of the lowest expressed, while the E1A isoform is highly predominant across cell types. To dissect SALL2 isoform-specific targets, we analyzed publicly available ChIP-seq data from Glioblastoma tumor-propagating cells and in-house ChIP-seq datasets performed in SALL2 wild-type and E1A isoform knockout HEK293 cells. Another available ChIP-seq data in HEK293 cells (ENCODE Consortium Phase III) overexpressing a non-canonical SALL2 isoform (short_E1A) was also analyzed. Regardless of cell type, our analysis indicates that the SALL2 long E1 and E1A isoforms, but not short_E1A, are mostly contributing to transcriptional control, and reveals a highly conserved network of brain-specific TFs (i.e., SALL3, POU3F2, and NPAS3). Our data integration identified a conserved molecular network in which SALL2 regulates genes associated with neural function, cell differentiation, development, and cell adhesion among others. Also, we identified PODXL as a gene that is likely regulated by SALL2 across tissues. Our study encourages the validation of publicly available ChIP-seq datasets to assess a specific gene/isoform's transcriptional targets. The knowledge of SALL2 isoforms expression and function in different tissue contexts is relevant to understanding its role in disease.